Ultra-short pulses generation using a carbon nanotubes saturable absorber / Dr. Amri Ab Rahman, PM. Dr. Mohd Nasir Ismail and Ahmad Bukhari Mohd Yasin - Ab Rahman, Amri; Ismail, Mohd Nasir; Mohd Yasin, Ahmad Bukhari (2017)
The field of fiber lasers and fiber optic devices has experienced a sustained rapid growth despite witnessing the infamous 'telecom bubble burst'. All-fiber optic devices have inherent advantages of relatively low cost, compact design, light weight, low maintenance, and increased vibration tolerances. In this research, Ultra Short Pulses Generation Using A carbon Nanotubes Saturable Absorber are investigated through experimental. At first, Q-switched Erbium-doped fiber lasers are demonstrated using a homemade passive saturable absorber (SA) based on single-walled carbon nanotubes (SWCNTs) and graphene oxide films. For instance, with the use of a SWCNTs-Polyvinyl alcohol (PVA) SA, the laser has a multi-wavelength output at 1533.5 nm region with a repetition rate of 13. I kHz, the pulse width of 7.2 µs and pulse energy of 21 nJ at the pump power of 64 mW. Two mode-locked EDFLs are also demonstrated using a homemade SA based on SWCNTs. For instance, a stable mode-locked EDFL is demonstrated using SWCNTs-PVA SA to generate a dissipative soliton pulse train operating in 1533.6 nm region. At pump power above the threshold value of 35.2 mW, the EDFL generates a self-starting pulse train with duration of 1.8 ps and repetition rate of 15.3 MHz. Besides showing good Q-switching and mode-locking performances, the proposed new saturable absorbers are easy to fabricate and cheap. Finally, the EDFL produces a fixed pulse width of 2.8 µs and harmonic pulse repetition rate of 58 kHz. Q- switched and mode-locked EDFLs have wide and important applications in many fields such as optical communications, laser micro-machining, optical sensors and laser ablation.